Performance test of Pikohidro Cross flow Water Turbine using multilevel double penstock - Purwantono, Purwantono; Amin, Bahrul; Aziz, Abdul; Jasman, Jasman; Kurniawan, Andre (Teknomekanik, 2019)
This study aims to examine the performance of pico hydro scale cross flow water turbines using multilevel double penstock as a conductor of water flow. Multilevel double penstock is used to reduce the transportation process from highways that are affordable to four-wheeled vehicles / cars to the location of the installation of the turbine. This condition causes the need for small-scale water turbine designs with lightweight construction with a kock down system. Overall the picohidro scale turbine construction is needed relatively cheaper transportation costs, so that people who have not been reached by the PLN network can be touched by small and cheap electricity. Turbine construction data has a runner diameter of 170 mm, body dimensions 200 mm x 300 mm x 250 mm, frame 250 mm x 800 mm. Pool tando 600 mm x 1200 mm and penstock length 16m. The power produced is theoretically around 2500 watts, with a data flow of 50 liters / second and a water level of 8 m. 65% efficiency. The research method is analyzing the double penstock water flow, by making paralon pipes in stages, ranging from 5 incci diameter, 4 inches and 3 inches, flow analysis approach using a gradient line, where the incoming water velocity and water velocity come out until entering the transmitting pipe. The performance results of this turbine provide an average actual power of up to 2000 watts. The stability of the inlet water condition is used by the Tando pond as a water bath. If there is excess water in the sediment tank, the water gate is used out, where excess water will automatically flow into the exhaust channel.